Anti-inflammatory effects of the phosphodiesterase type 4 inhibitor CHF6001 on bronchoalveolar lavage lymphocytes from asthma patients. (January 2019) - Southworth, Thomas; Kaur, Manminder; Hodgson, Lynsey; Facchinetti, Fabrizio; Villetti, Gino; Civelli, Maurizio; Singh, Dave
Abstract: Background: Lymphocytes play a key role in asthma pathophysiology, secreting various cytokines involved in chronic inflammation. CHF6001 is a highly potent and selective phosphodiesterase type 4 (PDE4) inhibitor designed for inhaled administration and has been shown to reduce the late asthmatic response. However, the effect of PDE4 inhibition on the different cytokines produced by lung lymphocytes from asthma patients has not been examined. Methods: This study investigated the anti-inflammatory effects of CHF6001 and the corticosteroid, 17-BMP, on T-cell receptor (TCR) stimulated Th1, Th2 and Th17 cytokine release from bronchoalveolar lavage (BAL) cells from mild (n = 12) and moderate asthma (n = 12) patients. Results: CHF6001 inhibited IFNγ, IL-2 and IL-17, but not IL-13, secretion from both mild and moderate asthma patient BAL cells; there was a greater effect on IFNγ and IL-2 than IL-17. The corticosteroid inhibited all four cytokines from both patient groups, but was less effective in cells from more severe patients. CHF6001 had a greater inhibitory effect on IFNγ and IL-2 than 17-BMP. Conclusion: The PDE4 inhibitor CHF6001 had a greater effect on Th1 cytokines from TCR-stimulated BAL cells than corticosteroid. This pharmacological effect suggests the therapeutic potential for PDE4 inhibitors to be used in the subset of more severe asthma patients with increased airway levels of IFNγ.